2021
DOI: 10.3389/fnut.2021.660420
|View full text |Cite|
|
Sign up to set email alerts
|

Low Serum 25-hydroxyvitamin D (Vitamin D) Level Is Associated With Susceptibility to COVID-19, Severity, and Mortality: A Systematic Review and Meta-Analysis

Abstract: Background: This systematic review and meta-analysis aimed to assess whether low serum 25-hydroxyvitamin D (25-OHD) level is associated with susceptibility to COVID-19, severity, and mortality related to COVID-19.Methods: Systematic literature searches of PubMed, Scopus, and Embase database up until 9 December 2020. We include published observational prospective and retrospective studies with information on 25-OHD that reported main/secondary outcome. Low serum 25-OHD refers to participants with serum 25-OHD l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 41 publications
3
54
1
2
Order By: Relevance
“…As is the case with COVID-19 infection, there is ample data to suggest that vitamin D deficiency is associated with COVID-19 severity and mortality [4][5][6]33]. Although contradictory literature exists wherein the relationship between vitamin D and COVID-19 has been negated [13], several systematic reviews and meta-analyses, albeit based on observational studies, suggest a consistent negative association between serum 25-hydroxyvitamin D levels and COVID-19 disease severity [3,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with COVID-19 infection, there is ample data to suggest that vitamin D deficiency is associated with COVID-19 severity and mortality [4][5][6]33]. Although contradictory literature exists wherein the relationship between vitamin D and COVID-19 has been negated [13], several systematic reviews and meta-analyses, albeit based on observational studies, suggest a consistent negative association between serum 25-hydroxyvitamin D levels and COVID-19 disease severity [3,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…While nutrition may theoretically impact COVID-19 susceptibility [3,6,[30][31][32], few investigations have specifically tested the hypothesis a priori. Low vitamin D status is associated with COVID-19 infection, severity, and mortality [33,34]. Del Ser et al [35] recently explored a variety of risk factors for the incidence, severity, and mortality of COVID-19 in a Spanish cohort of 913 volunteers aged 75-90 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vitamin D insufficiency [i.e., serum 25 (OH)D level 20-29.9 ng/mL] or deficiency [serum 25(OH)D level < 20 ng/mL] are associated with increased infection susceptibility, increased cancer incidence, poor survival of cancer patients, and development of autoimmune diseases (34,36,37). For example, recent studies suggested that vitamin D insufficiency and deficiency were associated with increased susceptibility to COVID-19 and severe presentation and mortality from it (38)(39)(40). Vitamin D, having an immune modulatory function, is considered to reduce the production of pro-inflammatory cytokines, thus, reducing the severity and mortality of COVID-19 (35).…”
Section: Discussionmentioning
confidence: 99%